2022
DOI: 10.1097/eja.0000000000001776
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and factors associated with ICU mortality during the first year of the SARS-Cov-2 pandemic in Romania

Abstract: BACKGROUND The epidemiology of critically ill patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) may be different worldwide. Despite similarities in medicine quality and formation, there are also significant differences concerning healthcare and ICU organisation, staffing, financial resources and population compliance and adherence. Large cohort data of critically ill patients from Central and Eastern Europe are also lacking.OBJECTIVES The study objectives were to describe the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…Numerous studies, underscored by two meta-analyses, have demonstrated the frequent occurrence of COVID-AKI, especially among critically ill patients, evidencing an average incidence rate of 11% (8–17%) among hospitalized patients, and up to 23% (14–35%) for those requiring admission to the intensive care unit (ICU) [ 11 , 12 ]. Building upon this, a recent study by Bubenek-Turconi et al on a Romanian cohort of 9058 ICU-admitted COVID-19 patients unveiled a 24.1% prevalence of COVID-AKI[ 13 ]. Noteworthy, in the subset of the very elderly patients, the same authors found that COVID-AKI emerged as the second most prevalent complication (27%), surpassed only by ARDS with an incidence of 33% [ 14 ].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies, underscored by two meta-analyses, have demonstrated the frequent occurrence of COVID-AKI, especially among critically ill patients, evidencing an average incidence rate of 11% (8–17%) among hospitalized patients, and up to 23% (14–35%) for those requiring admission to the intensive care unit (ICU) [ 11 , 12 ]. Building upon this, a recent study by Bubenek-Turconi et al on a Romanian cohort of 9058 ICU-admitted COVID-19 patients unveiled a 24.1% prevalence of COVID-AKI[ 13 ]. Noteworthy, in the subset of the very elderly patients, the same authors found that COVID-AKI emerged as the second most prevalent complication (27%), surpassed only by ARDS with an incidence of 33% [ 14 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…The incidence varies significantly between studies, with the highest reported rates seen in North America and Europe [ 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ](see Table 1 ). This variation is largely attributed to several factors, including the inconsistent use of the KDIGO staging for AKI, irregular measurement or reporting of baseline serum creatinine, ambiguity concerning recent renal function history, differences in study populations, failure to differentiate between de novo AKI and acute-on-chronic kidney disease, reporting bias, and timing of data collection.…”
Section: Epidemiologymentioning
confidence: 99%
“…The clinical status and severity were similar between the two groups regarding the initial ICU admission (SOFA score, dyspnea, fever, ARDS, need for MV) and management, excepting the neurological status (Table 1). The non-vaccinated patients had a lower Glasgow Coma Scale (GCS) compared to the vaccinated group (15 [7][8][9][10][11][12][13][14][15] vs. 15 [12][13][14][15], p = 0.010). Mortality was lower for vaccinated patients compared to non-vaccinated patients (58% vs. 67%, p = 0.045), while the ICU length of stay was similar between vaccinated and non-vaccinated patients.…”
Section: Characteristics Of Fully Vaccinated Patients Admitted In Icumentioning
confidence: 99%
“…The multivariate logistic regression analysis with ICU mortality as the dependent variable (Table 3) found that the vaccinated status, OR 0.54, 95% CI (0.31-0.93), p = 0.027, and higher GCS on admission, OR 0.9, 95% CI (0.85-0.92), p < 0.001 were factors independently associated with ICU survival. The same multivariate logistic regression analysis showed that ischemic heart disease, OR 1.9, 95% CI (1.4-2.6), p < 0.001, chronic kidney disease, OR 2.2, 95% CI (1.5-3.3), p < 0.001, admission SOFA, OR 1.03, 95% CI (1.01-1.06), p = 0.003, the need for non-invasive ventilation, OR 2, 95% CI (1.6-2.7), p < 0.001, and the need for invasive mechanical ventilation, OR 14, 95% CI (11)(12)(13)(14)(15)(16)(17)(18), p < 0.001 were factors independently associated with ICU mortality.…”
Section: Risk Factors For Icu Mortalitymentioning
confidence: 99%
See 1 more Smart Citation